Development of a Genome-Edited Tomato With High Ascorbate Content During Later Stage of Fruit Ripening Through Mutation of SlAPX4 - Do, Ju Hui; Park, Seo Young; Park, Se Hee; Kim, Hyun Min; Ma, Sang Hoon; Mai, Thanh Dat; Shim, Jae Sung; Joung, Young Hee (Frontiers in Plant Science, 2022)
Ascorbate is an essential antioxidant substance for human. Due to lack of ascorbate biosynthetic enzyme, human must intake ascorbate from food source. Tomato is one of the most widely consumed fruits, thus elevation of ascorbate content in tomato fruits will improve their nutritional value. Here we characterized Solanum lycopersicum ASCORBATE PEROXIDASE 4 (SlAPX4) as a gene specifically induced during fruit ripening. Ascorbate content analysis during fruit maturation showed thatIn tomato, ascorbate accumulates in yellow stage of fruits, then decreases during later stages of fruit ripening. To investigate whether SlAPX is involved in the decrease of ascorbate, expression of SlAPXs was analyzed during fruit maturation. Among nine SlAPXs, SlAPX4 is the only gene whose expression was induced during fruit ripening. Mutation of SlAPX4 by the CRISPR/Cas9 system increased ascorbate content in ripened tomato fruits, while ascorbate content in leaves was not significantly changed by mutation of SlAPX4. Phenotype analysis revealed that mutation of SlAPX4 did not induce adverse effect on the growth of tomato plants. Collectively, we suggest that SlAPX4 mediates decrease of ascorbate content during later stage of fruit ripening, and mutation of SlAPX4 can be used for development of genome edited tomato with elevated ascorbate content in fruits.